Landscape - Seascape - Cityscape - Monett, Alexandra; New York Academy of Art, New York (New Orleans : Contemporary Arts Center, 1986)
Abraham, Kim ; Alsop, Adele ; Anderson, Brooks ; Andrejevic, Milet ; Appel, Karel ; Barnes,Robert ; Beal, Jack ; Beckman, William ; Behnke, Leigh ; Berlind, Robert ; Birmelin, Robert ; Blaine, Nell ; Brandt, Warren ; Brown, Roger ; Chase, Louisa ; Chiriani, Richard ; Clark, Emery ; etc.
Landscape - Seascape - Cityscape, Contemporary Arts Center, New Orleans, January 18 - March 9, 1986 ; New York Academy of Art, New York, March 20 - April 30, 1986
boek